2008
DOI: 10.2353/ajpath.2008.070850
|View full text |Cite
|
Sign up to set email alerts
|

Cortical Demyelination Is Prominent in the Murine Cuprizone Model and Is Strain-Dependent

Abstract: The cuprizone model of toxic demyelination in the central nervous system is commonly used to investigate the pathobiology of remyelination in the corpus callosum. However, in human demyelinating diseases such as multiple sclerosis, recent evidence indicates a considerable amount of cortical demyelination in addition to white matter damage. Therefore, we have investigated cortical demyelination in the murine cuprizone model. To induce demyelination, C57BL/6 mice were challenged with 0.2% cuprizone feeding for 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

24
193
3
7

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(229 citation statements)
references
References 32 publications
24
193
3
7
Order By: Relevance
“…In previous studies on aged monkey brains, two of the age-related alterations seen in this study in myelin sheaths (local splitting of the major dense lines and the formation of myelin balloons) were observed in the anterior commissure, primary visual cortex and corpus callosum (Peters et al, 2000;Peters and Sethares, 2002;Sandell and Peters, 2003). Moreover, it has been reported that myelin sheath changes were also involved in various diseases (Lassmann et al, 1997;Myers, 1998;Biffiger et al, 2000), and in various experimental conditions (Blakemore, 1978;Chang, 1990;Anderson et al, 1998;Franco-Pons et al, 2007;Karim et al, 2007;Skripuletz et al, 2008;). Similar age-related changes in the myelin sheaths of elderly rats were observed in this study (Fig.4A, Fig.4B).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies on aged monkey brains, two of the age-related alterations seen in this study in myelin sheaths (local splitting of the major dense lines and the formation of myelin balloons) were observed in the anterior commissure, primary visual cortex and corpus callosum (Peters et al, 2000;Peters and Sethares, 2002;Sandell and Peters, 2003). Moreover, it has been reported that myelin sheath changes were also involved in various diseases (Lassmann et al, 1997;Myers, 1998;Biffiger et al, 2000), and in various experimental conditions (Blakemore, 1978;Chang, 1990;Anderson et al, 1998;Franco-Pons et al, 2007;Karim et al, 2007;Skripuletz et al, 2008;). Similar age-related changes in the myelin sheaths of elderly rats were observed in this study (Fig.4A, Fig.4B).…”
Section: Discussionmentioning
confidence: 99%
“…A number of reports have indicated that this demyelination model also displays abnormal behaviors and cognitive defects that are believed to be a direct result of demyelination [28,29,37,38] . The behavior changes may reflect neuronal abnormalities, like anxiety and cognitive impairment, and mimic, at least partially, schizophrenia symptoms in humans.…”
Section: Resultsmentioning
confidence: 99%
“…39 Following the confirmation of the efficacy of this model of toxic demyelination in the CNS, the polyplex formulations were injected followed by imaging the animal at 0, 15, 30, 60, 120, 180 min, and 24 h post injection. Figure 7 shows the distribution of the fluorescently labeled plasmid encoding CD200 from the injection site to the various tissues and organs including the lymph nodes, liver, brain, and finally kidneys.…”
Section: Fluorescent Microscopy and In Vivo Imaging In Mouse Model Of Msmentioning
confidence: 99%
“…The demyelination was confirmed by Luxol Fast Blue staining according to Kluver-Barrera procedure as described elsewhere. 39 To track nanoparticles in the body of the mice, fluorescently labeled plasmid encoding CD200 by GelRed was used, and the polyplexes at the highest C/P ratio of 8 were prepared as described earlier (vide supra). Mice were injected via the tail vein at a final volume of 100 μL of the polyplex formulation.…”
mentioning
confidence: 99%